The Emergence of an Alternative Milieu: Conceptualising the Nature of Alternative Places. (September 2013) - Longhurst, Noel
This paper introduces the concept of an alternative milieu in order to provide a more thorough account of the nature and development of 'alternative' places. It argues that such places have been generally neglected within geography, and that where they have been the object of research it is usually through a narrow conceptual lens. It is argued that the concept of an alternative milieu provides three analytical benefits. Firstly, it highlights the diversity of alterity within a given locality, a factor that is obscured by simplistic place images or narrower analytical frames. Secondly, it emphasises the significance of geographically fixed institutions in the formation of alternative places. Thirdly, it provides an anchor concept around which the processes that lead to the formation of alternative places can be orientated. The utility of the concept is illustrated through a case study of the emergence of an alternative milieu around the market town of Totnes in the United Kingdom.